A cemented carbide with a network structure and a method of manufacturing
Patent Information
- Application Number
- CN202611029035.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-10
- Publication Date
- 2026-10-23
AI Technical Summary
[0005]本发明要解决的主要技术问题是针对现有网状结构硬质合金中团粒骨架均一性不足,大小存在明显差异,容易引起合金性能不稳定等不足,提供一种网状结构硬质合金的制备方法
本发明采用压制成条、切粒和球磨工艺,制备成粒径均匀、颗粒完整的球形团粒结构料,该方法所得的团粒结构料与网状基体结构料具有良好的相容性,团粒结构料在与网状基体结构料混合、压制成型、烧结过程中,能够保持良好的均匀性、完整性和粒径均一性,既能够保证材料硬度的前提下有效提升材质的韧性,又能提高网状合金性能的一致性、稳定性,降低工业批量化生产的性能波动,提高产品质量。
Smart Images

Figure CN122959593A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the technical field of preparing network structure cemented carbide, and more specifically, to a network structure cemented carbide and its preparation method. Background Technology
[0002] Cemented carbide possesses excellent properties such as high hardness, strong compressive strength, and good wear resistance. However, the toughness and wear resistance of cemented carbide are contradictory properties. Generally, the higher the cobalt content and the coarser the tungsten carbide grain size, the better the toughness of the cemented carbide, but the worse the wear resistance. Conversely, the lower the cobalt content and the finer the tungsten carbide grain size, the worse the toughness, but the better the wear resistance. Traditional cemented carbide typically employs a microstructure in which WC particles are uniformly distributed on a cobalt binder matrix. Cemented carbides with this microstructure rarely possess both excellent toughness and wear resistance simultaneously.
[0003] In network-structured cemented carbide, cobalt and tungsten carbide are not uniformly distributed, but rather "high-hardness agglomerates" are uniformly distributed within a "high-toughness matrix," forming a unique microstructure with a dual-scale composite effect. The uniformly distributed cemented carbide agglomerates act as a skeleton, providing high wear resistance. As long as the agglomerates remain intact, wear is mainly limited to the agglomerates themselves and the surrounding softer matrix area, avoiding large-area, rapid material loss. The tough matrix effectively absorbs and disperses external impact energy, preventing crack initiation and propagation, and providing high toughness. In this way, the network structure maintains the alloy's wear resistance while improving its overall toughness, effectively resolving the contradiction between wear resistance and toughness. For example, CN101787479B discloses a method for preparing a network structure cemented carbide using 3.5–6 wt% cobalt, less than 2 wt% TaC, and the balance WC to prepare agglomerates. A slurry containing 6–10 wt% cobalt, less than 1 wt% TaC, and the balance WC is used as the network matrix. The two are mixed, dried, pressed into shape, and finally sintered to form a network structure cemented carbide. In this patent, the network structure cemented carbide is prepared with a higher-hardness cemented carbide as agglomerates and a lower-hardness cemented carbide as the network matrix. Because the cemented carbide agglomerates have high hardness, they exhibit good wear resistance, while the matrix has low hardness and good toughness, thus achieving a balance between high wear resistance and high toughness. However, the microstructure photograph (X500) of the prepared network structure cemented carbide shows that the skeleton formed by the agglomerates is unevenly dispersed, and the agglomerate skeleton has an irregular shape, not being a complete spherical agglomerate. Maintaining the integrity and uniform dispersion of the agglomerates is crucial for maintaining high wear resistance.
[0004] CN111270121B discloses a method for preparing and applying a network-structured cemented carbide using a "vacuum thermosetting + flexible mixing + low-pressure sintering" process. This ensures thorough and uniform mixing of the granular material, matrix material, forming agent, and other additives, guaranteeing the integrity of the spherical structure of the granules and the uniformity of their distribution within the matrix. The resulting network-structured cemented carbide exhibits no A or B type porosity defects in its metallographic structure, and its comprehensive mechanical properties are significantly superior to those of traditional cemented carbides using granular and matrix materials. While this patent utilizes vacuum thermosetting to create sintering necks between raw material powder particles, thereby giving the granules a certain strength and ensuring their intact spherical structure, and largely guarantees the integrity of the sintered granules, the microstructure of the network-structured cemented carbide, formed by spray drying, still reveals variations in the size of the granule skeleton. This uneven granulation leads to unstable performance of the final network-structured alloy, resulting in an unstable end-life. In addition, vacuum thermosetting of granules at a high temperature of 1200℃ can reduce the compatibility between granules and matrix, leading to problems such as cracks. Summary of the Invention
[0005] The main technical problem to be solved by the present invention is to address the shortcomings of existing network structure cemented carbide, such as insufficient uniformity of the aggregate skeleton, significant differences in size, and easy instability of alloy properties. The present invention provides a method for preparing network structure cemented carbide.
[0006] The objective of this invention is achieved through the following technical solution: A method for preparing a network-structured cemented carbide, comprising the following steps: S1. Preparation of the mesh matrix structure material: Tungsten carbide powder, cobalt powder and forming agent are mixed, ball-milled and spray-dried to obtain the mesh matrix structure material; S2. Preparation of granular material: S21. Tungsten carbide powder, cobalt powder and forming agent are mixed, ball-milled and dried to obtain a mixture, and the mixture is extruded in a mold to obtain a strip; S22. Granulated material obtained by cutting long strips into pellets and then pelletizing them; S3. Mixing: Mix the granular structure material and the network matrix structure material evenly, and then press them into shape to obtain the blank; S4. Sintering: Sintering the billet to obtain a network structure cemented carbide.
[0007] Furthermore, the tungsten carbide powder content in the mesh matrix structure material is 80-85%, and the cobalt powder content is 15-20%.
[0008] Furthermore, the average grain size of the carbide is 2.0–4.0 μm, and the particle size of the cobalt powder is 0.8–1.3 μm.
[0009] Furthermore, the granular material contains 88-93% tungsten carbide powder and 7-12% cobalt powder.
[0010] Furthermore, the average grain size of the carbide is 1.0–2.0 μm, and the particle size of the cobalt powder is 0.8–1.3 μm.
[0011] Furthermore, the molding agent includes paraffin or polyethylene glycol.
[0012] Furthermore, the amount of the forming agent added is 2-8% of the mass of the cemented carbide powder.
[0013] Furthermore, the ball-to-material ratio in S1 is 2:1; the ball-to-material ratio in S21 is 4:1.
[0014] Furthermore, the mixture is first pre-extruded through an extrusion orifice with a diameter of 2-3 mm, and then extruded through an orifice with a diameter of 0.4-0.6 mm to obtain strips.
[0015] Furthermore, the granulated material is ball-milled for 12-18 hours in a ball mill with a ball-to-material ratio of 3:1 and a ball diameter of Φ3mm:Φ5mm=1:1.
[0016] Furthermore, the mass ratio of the granular structure material to the network matrix structure material is 6~7:3~4.
[0017] Further, the sintering includes: First stage sintering: The temperature is increased from room temperature to 600℃ at a rate of 1~3℃ / min, held for 30~60min, and hydrogen is introduced during the heating process; Second stage sintering: Vacuum the gas out of the furnace, heat up to 1350℃ at a heating rate of 4~5℃ / min, and hold for 30~60min; The third stage of sintering: First, heat the temperature to 1450℃ at a heating rate of 1~2℃ / min, hold for 10~30min, then fill with inert gas and hold at temperature and pressure for 60~120min.
[0018] Furthermore, the furnace pressure in the first sintering stage is maintained at a relative pressure of not less than 20 mbar; the furnace pressure in the second sintering stage is not higher than 0.35 mbar; and the furnace pressure during the heating process in the third sintering stage is -960 mbar, while the pressure of the inert gas is 55~60 mbar.
[0019] A network-structured cemented carbide is prepared according to the above method.
[0020] Compared with existing technologies, the beneficial effects are: This invention employs pressing, pelletizing, and ball milling processes to prepare spherical agglomerated material with uniform particle size and complete particle structure. The agglomerated material obtained by this method has good compatibility with the network matrix material. During the mixing, pressing, and sintering process with the network matrix material, the agglomerated material can maintain good uniformity, integrity, and particle size uniformity. This not only ensures the hardness of the material but also effectively improves the toughness of the material, enhances the consistency and stability of the network alloy's performance, reduces performance fluctuations in industrial mass production, and improves product quality. Attached Figure Description
[0021] Figure 1 This is a schematic diagram of the fabrication process for a network-structured cemented carbide.
[0022] Figure 2 The image shown is a metallographic scanning electron microscope image at 100x magnification in the example.
[0023] Figure 3 The image shown is a metallographic scanning electron microscope image at 1500x magnification in the example. Detailed Implementation
[0024] The following examples further explain and clarify the invention, but the specific examples do not limit the invention in any way.
[0025] Example 1 This embodiment provides a method for preparing a network-structured cemented carbide, the steps of which include: S1. Preparation of the mesh matrix structure material: Tungsten carbide powder with an average grain size of 2.0–4.0 μm accounted for 84% of the total weight, cobalt powder with a grain size of 0.8–1.3 μm accounted for 16% of the total weight, 56# paraffin wax with a grain size of 2% of the weight of cemented carbide raw material was added as a forming agent, and 2.0% alcohol was added. The mixture was ball-milled for 24 hours at a ball-to-material ratio of 2:1, and then spray-dried and granulated to obtain a network matrix structure material.
[0026] S2. Preparation of granular material: S21. Take 90% of the total weight of tungsten carbide powder with an average grain size of 1.0-2.0 μm, 10% of the total weight of cobalt powder with a grain size of 0.8-1.3 μm, add 2.0% of cemented carbide 56# paraffin molding agent and alcohol, wherein the alcohol coefficient is 250 ml / kg, and ball mill at a ball-to-powder ratio of 4:1 for 40 hours to obtain a slurry.
[0027] S21. After the slurry is passed through a 200-mesh sieve and dried, and after it is fully cooled, add 6.0% paraffin solution and continue to stir evenly. Pre-extrude the muddy slurry. Use a mold with a single hole diameter of 2.5mm to pre-extrude the mixture 4 times. Then, use a die with an extrusion nozzle diameter of 0.5mm to extrude the material into long strips.
[0028] S22. Use a cutting machine to cut the strip into granules with a length of 0.5~0.6mm, and then put the granules into a ball mill with steel ball diameters of Φ3mm:Φ5mm=1:1, and ball mill at a speed of 65rpm / min for 15h to obtain agglomerated material.
[0029] S3. Mixing: Mix the granular structure material and the network matrix structure material at a mass ratio of 6:4 for 20 minutes until they are evenly mixed, and then press them into shape to obtain the blank. S4. Sintering: First stage sintering: The temperature is increased from room temperature to 600℃ at a heating rate of 2℃ / min, held for 30min, and hydrogen is introduced during the heating process at a flow rate of 60 L / min. The pressure inside the furnace is maintained at a relative pressure of not less than 20 mbar.
[0030] Second stage sintering: Vacuum the gas out of the furnace, the pressure inside the furnace should not exceed 0.35 mba, heat to 1350℃ at a heating rate of 5℃ / min, and hold for 30min; The third stage of sintering: the temperature is raised to 1450℃ at a heating rate of 2℃ / min, and the pressure inside the furnace is maintained at -960mbar. The temperature is held for 20min, and then Ar inert gas is introduced. The gas pressure inside the furnace is controlled at 58bar, and the temperature is held at 1450℃ for 60min.
[0031] After sintering and cooling, a network-structured cemented carbide is obtained.
[0032] Example 2 This embodiment provides a method for preparing a network-structured cemented carbide, the steps of which include: S1. Preparation of the mesh matrix structure material: Tungsten carbide powder with an average grain size of 2.0–4.0 μm accounted for 84% of the total weight, cobalt powder with a grain size of 0.8–1.3 μm accounted for 16% of the total weight, 56# paraffin wax with a grain size of 2% of the weight of cemented carbide raw material was added as a forming agent, and 2.0% alcohol was added. The mixture was ball-milled for 24 hours at a ball-to-material ratio of 2:1, and then spray-dried and granulated to obtain a network matrix structure material.
[0033] S2. Preparation of granular material: S21. Take 90% of the total weight of tungsten carbide powder with an average grain size of 1.0-2.0 μm, 10% of the total weight of cobalt powder with a grain size of 0.8-1.3 μm, add 2.0% of cemented carbide 56# paraffin molding agent and alcohol, wherein the alcohol coefficient is 250 ml / kg, and ball mill at a ball-to-powder ratio of 4:1 for 40 hours to obtain a slurry.
[0034] S21. After the slurry is passed through a 200-mesh sieve and dried, and after it is fully cooled, add 6.0% paraffin solution and continue to stir evenly. Pre-extrude the muddy slurry. Use a mold with a single hole diameter of 2.5mm to pre-extrude the mixture 4 times. Then, use a die with an extrusion nozzle diameter of 0.5mm to extrude the material into long strips.
[0035] S22. Use a cutting machine to cut the strip into granules with a length of 0.5~0.6mm, and then put the granules into a ball mill with steel ball diameters of Φ3mm:Φ5mm=1:1, and ball mill at a speed of 65rpm / min for 15h to obtain agglomerated material.
[0036] S3. Mixing: Mix the granular structure material and the network matrix structure material at a mass ratio of 7:3 for 20 minutes until they are evenly mixed, and then press them into shape to obtain the blank. S4. Sintering: First stage sintering: The temperature is increased from room temperature to 600℃ at a heating rate of 2℃ / min, held for 30min, and hydrogen is introduced during the heating process at a flow rate of 60 L / min. The pressure inside the furnace is maintained at a relative pressure of not less than 20 mbar.
[0037] Second stage sintering: Vacuum the gas out of the furnace, the pressure inside the furnace should not exceed 0.35 mba, heat to 1350℃ at a heating rate of 5℃ / min, and hold for 30min; The third stage of sintering: the temperature is raised to 1450℃ at a heating rate of 2℃ / min, and the pressure inside the furnace is maintained at -960mbar. The temperature is held for 20min, and then Ar inert gas is introduced. The gas pressure inside the furnace is controlled at 58bar, and the temperature is held at 1450℃ for 60min.
[0038] After sintering and cooling, a network-structured cemented carbide is obtained.
[0039] Comparative Example 1 This embodiment provides a mesh-structured cemented carbide with the same process parameters as the previous embodiment. The difference is that the granular material in this comparative embodiment is obtained by drying the slurry of tungsten carbide, cobalt, and forming agent and then sieving it to obtain granules.
[0040] The performance of the network structure cemented carbides prepared in the examples and comparative examples was tested, and the test results are shown in Table 1 below: Table 1
[0041] Based on Table 1 above Figures 1-2 It is evident that the present invention, through pressing into strips, pelletizing, and ball milling processes, can improve the particle size uniformity and spherical particle integrity of the agglomerated material. Simultaneously, the agglomerated material, without high-temperature curing, exhibits good compatibility with the network matrix. The network-structured cemented carbide prepared by this invention, while maintaining the same hardness standard as existing cemented carbides, shows significantly improved flexural strength and excellent wear resistance and toughness. Furthermore, in actual production, the present invention, by controlling the consistency of the agglomerated material, reduces the performance fluctuation values of the network-structured cemented carbide from different production batches, thereby improving the performance stability of the network-structured cemented carbide.
[0042] Example 3 This embodiment provides a method for preparing a network-structured cemented carbide, the steps of which include: S1. Preparation of the mesh matrix structure material: Tungsten carbide powder with an average grain size of 2.0–4.0 μm accounted for 80% of the total weight, cobalt powder with a grain size of 0.8–1.3 μm accounted for 20% of the total weight, 56# paraffin wax (5% by weight of cemented carbide raw material) was added as a forming agent, and 2.0% alcohol was added. The mixture was ball-milled for 24 hours at a ball-to-material ratio of 2:1, and then spray-dried and granulated to obtain a network matrix structure material.
[0043] S2. Preparation of granular material: S21. Take 88% of the total weight of tungsten carbide powder with an average grain size of 1.0-2.0 μm, take 12% of the total weight of cobalt powder with a grain size of 0.8-1.3 μm, add 2.0% of cemented carbide 56# paraffin molding agent and alcohol, wherein the alcohol coefficient is 250 ml / kg, and ball mill at a ball-to-powder ratio of 4:1 for 40 hours to obtain a slurry.
[0044] S21. After the slurry is passed through a 200-mesh sieve and dried, and after it is fully cooled, 3.0% paraffin solution is added and stirred evenly. The muddy and viscous slurry is pre-extruded. A mold with a single hole diameter of 2mm is used to pre-extrude the mixture 4 times. Then, a 0.4mm pore diameter extrusion nozzle mold is used to extrude the material into long strips.
[0045] S22. Use a cutting machine to cut the strip into granules with a length of 0.3~0.5mm, and then put the granules into a ball mill for 12 hours to obtain agglomerated material.
[0046] S3. Mixing: Mix the granular structure material and the network matrix structure material at a mass ratio of 7:3 for 20 minutes until they are evenly mixed, and then press them into shape to obtain the blank. S4. Sintering: First stage sintering: The temperature is increased from room temperature to 600℃ at a heating rate of 3℃ / min, held for 60min, and hydrogen is introduced during the heating process at a flow rate of 60 L / min. The pressure inside the furnace is maintained at a relative pressure of not less than 20 mbar.
[0047] Second stage sintering: Vacuum the gas out of the furnace, the pressure inside the furnace is not higher than 0.35 mba, heat to 1350℃ at a heating rate of 4℃ / min, and hold for 60min; The third stage of sintering: the temperature is raised to 1450℃ at a heating rate of 1℃ / min, and the pressure inside the furnace is maintained at -960mbar. The temperature is held for 10min, and then Ar inert gas is introduced. The gas pressure inside the furnace is controlled at 58bar, and the pressure is held at 1450℃ for 120min.
[0048] After sintering and cooling, a network-structured cemented carbide is obtained.
[0049] Example 4 This embodiment provides a method for preparing a network-structured cemented carbide, which differs from Embodiment 1 in that the preparation steps for the network matrix structure material and the granular structure material include: S1. Preparation of the mesh matrix structure material: Tungsten carbide powder with an average grain size of 2.0–4.0 μm accounted for 85% of the total weight, cobalt powder with a grain size of 0.8–1.3 μm accounted for 15% of the total weight, 56# paraffin wax with a grain size of 2% of the weight of cemented carbide raw material was added as a forming agent, and 2.0% alcohol was added. The mixture was ball-milled for 24 hours at a ball-to-material ratio of 2:1, and then spray-dried and granulated to obtain a network matrix structure material.
[0050] S2. Preparation of granular material: S21. 93% of the total weight of tungsten carbide powder with an average grain size of 1.0–2.0 μm and 7% of the total weight of cobalt powder with a grain size of 0.8–1.3 μm are added, along with 2.0% of cemented carbide 56# paraffin molding agent and alcohol, with an alcohol coefficient of 250 ml / kg. The mixture is ball-milled for 40 hours at a ball-to-powder ratio of 4:1 to obtain a slurry.
[0051] S21. After the slurry is passed through a 200-mesh sieve and dried, and after it is fully cooled, 3.0% paraffin solution is added and stirred evenly. The muddy and viscous slurry is pre-extruded. A mold with a single hole diameter of 3mm is used to pre-extrude the mixture 4 times. Then, a 0.6mm pore diameter extrusion nozzle mold is used to extrude the material into long strips.
[0052] S22. Use a cutting machine to cut the strip into granules with a length of 0.5~0.6mm, and then put the granules into a ball mill for 18 hours to obtain agglomerated material.
[0053] S3. Mixing: Mix the granular structure material and the network matrix structure material at a mass ratio of 7:3 for 20 minutes until they are evenly mixed, and then press them into shape to obtain the blank. S4. Sintering: First stage sintering: The temperature is increased from room temperature to 600℃ at a rate of 1℃ / min, held for 30min, and hydrogen is introduced during the heating process at a flow rate of 60 L / min. The pressure inside the furnace is maintained at a relative pressure of not less than 20 mbar.
[0054] Second stage sintering: Vacuum the gas out of the furnace, the pressure inside the furnace should not exceed 0.35 mba, heat to 1350℃ at a heating rate of 5℃ / min, and hold for 60min; The third stage of sintering: the temperature is raised to 1450℃ at a heating rate of 2℃ / min, and the pressure inside the furnace is maintained at -960mbar. The temperature is held for 30min, and then Ar inert gas is introduced. The gas pressure inside the furnace is controlled at 58bar, and the pressure is held at 1450℃ for 60min.
[0055] After sintering and cooling, a network-structured cemented carbide is obtained.
[0056] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. Those skilled in the art will recognize that other variations or modifications can be made based on the above description. It is neither necessary nor possible to exhaustively describe all embodiments here. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of the present invention should be included within the scope of protection of the claims of the present invention.
Claims
1. A method for preparing a network structure cemented carbide, characterized in that the steps include... include: S1. Preparation of the mesh matrix structure material: Tungsten carbide powder, cobalt powder and forming agent are mixed, ball-milled and spray-dried to obtain the mesh matrix structure material; S2. Preparation of granular material: S21. Tungsten carbide powder, cobalt powder and forming agent are mixed, ball-milled and dried to obtain a mixture, and the mixture is extruded in a mold to obtain a strip; S22. Granulated material obtained by cutting long strips into pellets and then pelletizing them; S3. Mixing: Mix the granular structure material and the network matrix structure material evenly, and then press them into shape to obtain the blank; S4. Sintering: Sintering the billet to obtain a network structure cemented carbide.
2. The method for preparing the network structure cemented carbide according to claim 1, characterized in that, The tungsten carbide powder content in the mesh matrix structure material is 80-85%, and the cobalt powder content is 15-20%; the average grain size of the carbide is 2.0-4.0 μm, and the particle size of the cobalt powder is 0.8-1.3 μm.
3. The method for preparing the network structure cemented carbide according to claim 1, characterized in that, The granular material contains 88-93% tungsten carbide powder and 7-12% cobalt powder; the average grain size of the carbide is 1.0-2.0 μm, and the particle size of the cobalt powder is 0.8-1.3 μm.
4. The method for preparing the network structure cemented carbide according to claim 1, characterized in that, The molding agent includes one or more of paraffin wax and polyethylene glycol; the amount of the molding agent added is 2 to 5% of the mass of the cemented carbide powder.
5. The method for preparing the network structure cemented carbide according to claim 1, characterized in that, The extrusion molding process is as follows: the mixture is first pre-extruded through an extrusion orifice with a diameter of 2-3 mm, and then extruded through an orifice with a diameter of 0.4-0.6 mm to obtain a strip.
6. The method for preparing the network structure cemented carbide according to claim 1, characterized in that, The pelletizing process includes: grinding the granulated material in a ball mill with a ball-to-material ratio of 3:1 and a ball diameter of Φ3mm:Φ5mm=1:1 for 12~18 hours.
7. The method for preparing the network structure cemented carbide according to claim 1, characterized in that, The mass ratio of the granular structure material to the network matrix structure material is 6~7:3~4.
8. The method for preparing the network structure cemented carbide according to claim 1, characterized in that, The sintering includes: First stage sintering: The temperature is increased from room temperature to 600℃ at a rate of 1~3℃ / min, held for 30~60min, and hydrogen is introduced during the heating process; Second stage sintering: Vacuum the gas out of the furnace, heat up to 1350℃ at a heating rate of 4~5℃ / min, and hold for 30~60min; The third stage of sintering: First, heat the temperature to 1450℃ at a heating rate of 1~2℃ / min, hold for 10~30min, then fill with inert gas and hold at temperature and pressure for 60~120min.
9. The method for preparing the network structure cemented carbide according to claim 8, characterized in that, During the first stage of sintering, the furnace pressure is maintained at a relative pressure of not less than 20 mbar; during the second stage of sintering, the furnace pressure is not higher than 0.35 mbar; during the heating process in the third stage of sintering, the furnace pressure is -960 mbar, and the pressure of the inert gas is 55~60 mbar.
10. A network structure cemented carbide, characterized in that, It is prepared by the method described in any one of claims 1 to 9.
Citation Information
Patent Citations
Network-structured cemented carbide and its preparation method
CN101787479B
A method for preparing and applying a network-structured cemented carbide
CN111270121B